Conductivity Enhancement of PVD-WS2 Films Using Cl2-Plasma Treatment Followed by Sulfur-Vapor Annealing - Keita Kurohara; Shinya Imai; Takuya Hamada; Tetsuya Tatsumi; Shigetaka Tomiya; Kuniyuki Kakushima; Kazuo Tsutsui; Hitoshi Wakabayashi (IEEE Journal of the Electron Devices Society)
The conductivity of tungsten disulfide (WS2) films using sputtering, which is a physical vapor deposition (PVD), was enhanced using a chlorine (Cl2)-plasma treatment and sulfur-vapor annealing (SVA). For WS2 films to be used in thermoelectric devices, its carrier concentration must be controlled. Therefore, we exposed WS2 films to Cl2-plasma as a doping method. In addition, SVA was performed to improve the crystallinity of the film and potentially introduce activating dopants. Consequently, the conductivity of the Cl2-plasma-treated PVD-WS2 films (0.440 S/m) more than doubled compared with that of an untreated PVD-WS2 film (0.201 S/m). The doping type in this experiment is considered to be n-type on the basis of a positive peak shift observed in the X-ray photoelectron spectra.